Comprehensive comparison of thirteen kinds of cytokine receptors from the endangered fish Chinese sturgeon (Acipenser sinensis). (October 2021) - Xu, Qiaoqing; Deng, Dan; Guo, Huizhi; Yuan, Hanwen; Zhang, Wenbing; Wang, Bei; Lu, Yishan; Chen, Dunxue; Zhang, Shuhuan
Abstract: The interferon receptor system in teleost fish is more complex than that in mammals. In the present study, we identified 13 cytokine receptor genes (10 interferon receptor genes and 3 IL10R2-like genes) from Chinese sturgeon ( Acipenser sinensis ) using RNA-sequencing. Sequence analysis indicated that these receptors had conserved domains, including signal peptides, FNⅢ, and transmembrane domains. Phylogenetic analysis suggested that they belonged to the cytokine receptor family. In the present study, we named them IFNAR1-like (CRFB5a, CRFB5b), IFNAR2-like (CRFB3a, CRFB3b), IFNGR1-like (IFNGR1), IFNGR2-like (CRFB6a, CRFB6b/IFNGR2-1, CRFB6c/IFNGR2-2, CRFB6d/IFNGR2-3, CRFB6e/IFNGR2-4) and IL10R2-like (CRFB4a, CRFB4b, CRFB4c), respectively. Constitutive expression analysis revealed that these receptor genes had potential functions in immune and non-immune tissue compartments. After stimulating with Poly (I:C), the expression fold changes of CRFB3a, CRFB4a, CRFB4b, CRFB5b, and CRFB6e / IFNGR2-4 in Chinese sturgeon were higher than those of other receptor genes, which revealed that these five genes had important functions in the immune process to resist virus invasion in the host. After stimulating with IFN gamma, the expression fold changes of CRFB3a, CRFB4a, and CRFB6b / IFNGR2-1 were higher than those other receptor genes. Based on other teleost fish interferon receptor models, we speculated that IFNAR1-like (CRFB5a, CRFB5b) and IFNAR2-like (CRFB3a, CRFB3b), comprised Chinese sturgeon type Ⅰ IFN receptors; and IFNGR1-like (IFNGR1) and IFNGR2-like (CRFB6/IFNGR2) comprised Chinese sturgeon type Ⅱ IFN receptors. Highlights: This report first described thirteen interferon receptors expression pattern from the endangered fish Chinese sturgeon. CRFB3a and CRFB3b in ancient fish have the similar function as CRFB1 and CRFB2 in other teleosts.